Variants in the CHRNA5–CHRNA3–CHRNB4 Region of Chromosome 15 Predict Gastrointestinal Adverse Events in the Transdisciplinary Tobacco Use Research Center Smoking Cessation Trial. Issue 2 (18th March 2019) - Culverhouse, Robert C; Chen, Li-Shiun; Saccone, Nancy L; Ma, Yinjiao; Piper, Megan E; Baker, Timothy B; Bierut, Laura J
Abstract: Introduction: Reducing adverse events from pharmacologic treatment is an important goal of precision medicine and identifying genetic predictors of adverse events is a step toward this goal. In 2012, King et al. reported associations between genetic variants and adverse events in a placebo-controlled smoking cessation trial of varenicline and bupropion. Strong associations were found between gastrointestinal adverse events and 11 variants in the CHRNA5–CHRNA3–CHRNB4 region of chromosome 15, a region repeatedly associated with smoking-related phenotypes. Our goal was to replicate, in an independent sample, the impact of variants in the CHRNA5–CHRNA3–CHRNB4 region on gastrointestinal adverse events and to extend the analyses to adherence and smoking cessation. Methods: The University of Wisconsin Transdisciplinary Tobacco Use Research Center (TTURC) conducted a multiarmed, placebo-controlled smoking cessation trial of bupropion and nicotine replacement therapy that included 985 genotyped European-ancestry participants. We evaluated relationships between our key variables using logistic regression. Results: Gastrointestinal adverse events were experienced by 31.6% TTURC participants. Each of the CHRNA5–CHRNA3–CHRNB4 associations from the King et al. study was found in TTURC, with the same direction of effect. Neither these variants nor the gastrointestinal adverse events themselves were associated with adherence to medication or successful smoking cessation. Conclusions: Variants in the CHRNA5–CHRNA3–CHRNB4 region of chromosome 15 are associated with gastrointestinal adverse events in smoking cessation. Additional independent variants in this region strengthen the association. The consistency between the results of these two independent studies supports the conclusion that these findings reflect biological response to the use of smoking cessation medication. Implications: The fact that our findings from the TTURC smoking cessation trial support the independent findings of King et al . suggest that associations of variants in the CHRNA5–CHRNA3–CHRNB4 region of chromosome 15 with gastrointestinal adverse events while taking medications for smoking cessation reflect biology. However, although adherence to medication was a strong predictor of successful smoking cessation in TTURC, neither adverse events nor the genetic variants associated with them predicted either adherence or successful cessation in this study. Thus, although we should strive to minimize adverse events during treatment, we should not expect that to increase successful smoking cessation substantially.